ANALISIS KEBIJAKAN AMERIKA SERIKAT DALAM PENGGUNAAN UNMANNED COMBAT AERIAL VEHICLE (UCAV) DI NIGER TAHUN 2018 - Dharmayasa, Dewa Ketut; Widya Nugraha, A.A. Bagus Surya; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT The terrorist attack that occurred in the United States on September 9, 2001 often remembered as the 9/11 tragedy, is the worst terrorist attack the United States has experienced in its history. In combating the terrorist groups for the responsibility for these attacks, the United States responded by launching a campaign against terrorism known as Global War on Terrorism by issuing military strategies as a form of implementation. To deal with increased terrorist activity in the Niger region, the United States uses a varied military strategy, one of those strategy is UCAV usage.This study analyzes and describes the reasons for changes in United States military policy using Unmanned Combat Aerial Vehicle (UCAV) in Niger in 2018. This study uses a rational choice framework and national security strategy to explain the reasons for changing military policy by using UCAV drones in Niger. The methodology used in this research is qualitative-explanative. Keywords : United States, Niger, National Military Strategy, Unmanned Combat Aerial Vehicle, UCAV